PERBEDAAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI DENGAN MENGGUNAKAN MEDIA YOUTUBE DI MA ANNAJAH PONPES AL HALIMY SESELA - Any Fatmawati; Nofisulastri Nofisulastri; Siti Rabiatul Adawiyah; Novia Sarita Devi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
This study aims to determine differences in student learning outcomes in biology learning by using youtube media at MA Annajah Ponpes Al Halimy Sesela. This study involved 53 students of class IX MA, with 27 students for the experimental class and 26 students for the control class. This type of research is a quasi-experimental with post-test only control group design and the determination of samples using purposive sampling. The data collected is the data of student learning outcomes and student responses after participating in biology learning using youtube media. Learning outcome data were analyzed using an independent test sample T-Test in significance 5% with SPSS 16.00 for windows. The results of the analysis of learning outcomes data show that p = 0.008, so that H0 is rejected and Ha is accepted, that is there is no difference between the average learning outcomes of group A who follow the learning with youtube media and group B with learning not to use youtube media. The conclusion from this study is that there are differences in learning outcomes between students who take learning using Youtube media and students who take conventional learning (without Youtube) at MA Annajah Ponpes Al Halimy Sesela.